Protein - water interactions : a differential approach - Sirotkin, Vladimir A. (Protein biochemistry, synthesis, structure, and cellular functions series., 2014)
This book is aimed at understanding which molecular parameters control the thermodynamics, structure, and functions of the protein-water systems. Proteins are one of the most important classes of biological molecules. Water binding (hydration or biological water) plays a crucial role in determining the structure, stability, and functions of proteins. Knowledge of processes occurring upon hydration or dehydration of protein macromolecules is very important in biotechnological and pharmaceutical applications of proteins such as their use as biocatalysts, biosensors, and selective adsorbents. The.